KARAKTERISASI PLASMA JET ARGON MENGGUNAKAN KOLOM DIELECTRIC BARRIER DISCHARGE (DBD) PADA TEKANAN ATMOSFER - Andi Wibowo Kinandana; Muhammad Nur; Zaenul Muhlisin (Youngster Physics Journal, 2015)
An atmospheric of Argon plasma jet is generated with column dielectric barrier discharge high voltage alternating current. Characterization of Argon plasma jet is used to observe the effect of variations in the voltage (V) to the length of the plasma jet. Voltage (V) and current (I) were analyzed to identify its effect to the length of the plasma jet. In this study, Argon gas is passed through the capillary column by regulating the flow rate of gas. Then the voltageis being increased until the plasma jet can be seen. Voltage is used consecutively in the range 0 to 10,5 kV at flow rate of Argon gas is 3 L / min. The result shows that electrical current increase and then reach saturation condition by the increase of voltage. The increase of the length of the plasma jet were given by the increase of the applied voltage. This research indicates that the length of the plasma jet characteristics tends to increase. The value of the voltage is affects to the value length of the plasma jet.